Classical Music : The Great Composers and their Masterworks - Stanley, John (London Mitchell Beazley, 2005)
This invaluable reference book explores the background to 800 years of musical history - from 12th-century chanting monks to 19th-century virtuoso performers. This brand new edition has been fully revised to include today's iconoclastic composer-artists - and explains the origins and impact of the great classical masterpieces.
Include Index, Glossary and Illustration
Keywords: Music -- Music appreciation -- Composers